In situ generation of 3D graphene-like networks from cellulose nanofibres in sintered ceramics. Issue 22 (25th May 2018) - Kocjan, Andraž; Schmidt, Rainer; Lazar, Ana; Prado-Gonjal, Jesús; Kovač, Janez; Logar, Manca; Mompean, Francisco J.; Garcia-Hernandez, Mar; Ruiz-Hitzky, Eduardo; Wicklein, Bernd
Abstract : 3D graphene-like networks generated in situ from cellulose nanofibres enhance the electrical, dielectric and mechanical properties of engineering ceramics. Abstract : Establishing a 3D electrically percolating network in an insulating matrix is key to numerous engineering and functional applications. To this end, using hydrophobic carbon nanofillers is tempting, but still results in suboptimal performance due to processing challenges. Here, we demonstrate how natural cellulose nanofibres can be in situ transformed into graphene-like sheets connected to a 3D network enhancing both the transport and the mechanical properties of sintered engineering ceramics. The network architecture also permits the decoupling of electrical and thermal conductivities, which represents a major obstacle in attaining efficient thermoelectric materials. We foresee that our transferable methodology can pave the way for the use of natural nanofibres to unravel the full potential of 3D graphene-like networks to accelerate development in fields like energy and telecommunications.